Comprehensive evaluation of extemporaneous preparation containing ambroxol HCl and salbutamol sulfate: Compatibility, chemometrics, and stability study - Michael Raharja Gani, Jeffry Tanriono, Florentinus Dika Octa Riswanto, Dina Christin Ayuning Putri, Dita Maria Virginia, Sri Hartati Yuliani (Journal of Applied Pharmaceutical Science, 2022)
Extemporaneous compounding preparations of divided powder were commonly prescribed in Indonesia. Since it is important to implement the Good Pharmacy Practices Guideline, the compounded preparations should be evaluated for several quality parameters. This study aimed to perform a comprehensive evaluation of extemporaneous compounding preparation containing ambroxol HCl and salbutamol sulfate, including compatibility, chemometrics, and stability study. A compatibility study was carried out by evaluating FTIR spectroscopy on functional group change during the interaction between drugs and excipients. A chemometric approach of multivariate calibration was conducted to build predictive content determination for ambroxol HCl and salbutamol sulfate. It was found that the selected models for ambroxol HCl and salbutamol sulfate were partial least squares (PLS) on second derivative spectra and PLS on Savitzky–Golay spectra, respectively. The equation of multivariate calibration for ambroxol HCl was y = 0.975x−0.089 (Rval 2 = 0. 989), whereas the equation of multivariate calibration for salbutamol sulfate was y = 0.970x−0.119 (Rval 2 = 0.943). These models were employed for content determination in the stability study. Divided powder preparation samples were stable during seven days of storage.
Keywords: Ambroxol HCl, compatibility, multivariate calibration, salbutamol sulfate, stability